2021
DOI: 10.2166/washdev.2021.130
|View full text |Cite
|
Sign up to set email alerts
|

The clean plan: analysing sanitation planning in India using the CWIS planning framework

Abstract: Sanitation in India has received national attention for over a decade, especially with the Swachh Bharat Mission (SBM) making it a political priority. However, due to the lack of appropriate sanitation planning practices, there have been little long-term gains made in urban sanitation beyond the ending of open defaecation. In this paper, we analyse the key barriers to sanitation planning, in India, in the context of the emerging paradigm of Citywide Inclusive Sanitation (CWIS). A mixed method approach of shit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Involving the community in the planning, construction, decisionmaking, and sustainability management of sanitation facilities is pivotal to their success and long-term viability. As highlighted by [22], active communities and stakeholders during the planning process emerge as key success factors for the sustainability of sanitation systems. Such a high community involvement leads to increased ownership within the community.…”
Section: Discussionmentioning
confidence: 99%
“…Involving the community in the planning, construction, decisionmaking, and sustainability management of sanitation facilities is pivotal to their success and long-term viability. As highlighted by [22], active communities and stakeholders during the planning process emerge as key success factors for the sustainability of sanitation systems. Such a high community involvement leads to increased ownership within the community.…”
Section: Discussionmentioning
confidence: 99%
“…In India and Bangladesh, the holistic approach of offsite and onsite is taken side by side (Narayan et al 2021a ). Citywide inclusive sanitation (CWIS) targets safe sanitation provision for everyone either connected by a centralized/decentralized sewerage system or utilizing OSS (Narayan et al 2021b ). The current policies in Pakistan are completely ignoring this component.…”
Section: Discussionmentioning
confidence: 99%
“…Exum et al (2020) found that, from 2016 to 2018, main OD practices in rural Rajasthan households decreased from 63.3% to 45.8%, and in urban households from 12.6% to 9.4%. Narayan et al (2021) conducted key informant interviews to identify barriers to latrine use, and found that unreliable financial support, inadequate planning capacities, and poor community involvement were major factors contributing to continued open defecation. Das and Crowley (2018) also found affordability to be a key hurdle to sanitation program success, though 70% of participants expressed willingness to pay Rs.25-100 ($0.30-1.20 USD) monthly for connection to a networked sewer system.…”
Section: Impacts Of Sbm On Odmentioning
confidence: 99%